The LATIHAN SENAM AEROBIK DAN PENGUKURAN TEKANAN DARAH DAN DENYUT NADI WARGA RT 09 RW 09 JATISARI JATIASIH KOTA BEKASI JAWA BARAT - toto aminoto; Dwi Agustina; achwan achwan (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Physical fitness is a condition that must be maintained by someone who wants health. With excellent health, you can carry out work activities to earn a living. The benefit of this community service is doing aerobic exercise, especially for body fitness, and measuring body fitness levels. Indicators of body fitness are normal blood pressure and pulse. In this community service activity, aerobic exercise, blood pressure, and pulse measurements were carried out. Almost all residents attended the aerobic exercise activities, while the measurement of blood pressure and pulse was based on a sampling technique using purposive sampling. This sampling technique is based on inclusion and exclusion criteria. The statistical analysis used is descriptive, that is, it only looks at the description of the condition of blood pressure and pulse before and after aerobic exercise. These results show that after aerobic exercise, blood pressure and pulse measurements were more stable than before exercise.